Clinical observations in TVT affected dogs treated with Vincristine sulphate - JAIN, ANITA; TIWARl, R P; TIWARI, S K; AWASTHl, M K (The Indian Journal of Animal Reproduction, 2023)
Six healthy and six TVT affected dogs were treated with Vmcristine sulphate @0.025 mg/ kg body wt, 1/V at weekly interval for 5 weeks while 6 TVT affected dogs were surgically operated and after one week they were treated with vincristine sulphate at same dose rate and interval for three weeks at weekly interval. Five (83. 33%) animals recovered completely between two to five weeks period while one dog that was having extragenital metastasis did not recover in vincristine sulphate treated group. All the dogs (6/6) recovered completely without recurrence with surgical excision of tumour followed by vincristine sulphate administration. Side effects of vincristine sulphate injection included vomition, constipation, anorexia and alopecia. There ’Yas significant rise of body temperature (P<O .0 I) with nonsignificant increase in pulse and respiration rate following administration of vincristine sulphate. However, these side effects were transient and well tolerated by the treated animal.